PTX3 mediates the infiltration, migration, and inflammation‐resolving‐polarization of macrophages in glioblastoma. (20th July 2022) - Zhang, Hao; Wang, Yifan; Zhao, Yihan; Liu, Tao; Wang, Zeyu; Zhang, Nan; Dai, Ziyu; Wu, Wantao; Cao, Hui; Feng, Songshan; Zhang, Liyang; Cheng, Quan; et al.
Abstract: Introduction: Pentraxin 3 (PTX3) is an essential regulator of the immune system. However, the immune‐modulatory role of PTX3 in the tumor microenvironment of glioma has not been elucidated. Methods: The RNA seq samples were obtained from The Cancer Genome Atlas (TCGA) and the China Glioma Genome Atlas (CGGA) datasets. The single‐cell sequencing data of glioblastoma (GBM) samples were obtained from the Single Cell Portal platform (http://singlecell.broadinstitute.org ). Immunohistochemistry was used to assess PTX3 expression, HAVCR2, PD‐1, PD‐L1, and CD276 in glioma sections from the Xiangya cohort ( n  = 60). Multiplex immunofluorescence staining of PTX3, CD68, and CD163 was performed in several solid cancer types, including GBM. HMC3 was cocultured with U251 and U87, and transwell assay and flow cytometry assay were performed to explore the migration and polarization activity of HMC3. Results: PTX3 expression is significantly increased in GBM. PTX3 expression predicts worse survival in the Xiangya cohort. PTX3 is closely related to the expression of PD‐1, PD‐L1, CD276, and HAVCR2 in the tumor microenvironment. Additionally, PTX3 is involved in tumorigenic and immunogenic processes, especially the activity of macrophages based on various signaling pathways in cellular communications and critical transcription factors. Specifically, PTX3 actively mediates macrophages' infiltration, migration, and inflammation‐resolving‐polarization. PTX3 could also predict immunotherapy response. Conclusion: PTX3 is critically involved in macrophage infiltration, migration, and inflammation‐resolving‐polarization and modulates an immunosuppressive microenvironment. Abstract : In summary, we revealed the characteristics of PTX3 in the development of gliomas and the tumor immune microenvironment of cancer. The immunosuppressive property of PTX3 makes it a potential new therapeutic target and prognostic marker for the treatment of gliomas. Notably, PTX3 was found to mediate the infiltration, migration, and polarization of macrophages in GBM. Our study was expected to provide the background support for further in‐depth research about PTX3 in gliomas.